RADIO KAYU JEPARA - Nur Ikhsan; Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2019)
Radio is a plural item that is easy to find in various places. Radio has an important role in supporting all human activities. Either as an information medium or as an entertainment medium, the radio that the author created has been designed and made as an aesthetic object in a space.As a means of entertainment and information. This aims to provide other functions besides its main function. Based on this, the problems raised in this case are (1) How to design a radio design made of wood, which is capable of supporting human activities, (2) How to make a radio by including Jepara ornaments as decorative elements, which can be an attraction, socialization and appreciation.The use of the Jepara ornament is intended, so that Indonesian furniture designers should still care about the arts and culture of the archipelago, namely by applying handicraft products into it, so that it can become a medium of socialization and appreciation. of Indonesian culture, this can simultaneously preserve the culture